The possessions of Doctor Forrest : a novel - Kelly,Richard T (Faber & Faberd T, 2011)
The tradition of the Gothic novel comes alive once again in this spine chilling fable, the story of a disappearance, a diabolical bargain, and a terrifying series of physical transformations. Three respected Scottish doctors, psychiatrist Steve Hartford, paediatric surgeon Grey Lochran and cosmetic surgeon Robert Forrest, have been friends since their Edinburgh boyhoods, and now live comfortably in suburban London.